2005
DOI: 10.1016/j.jtcvs.2004.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid aspiration and the development of bronchiolitis obliterans after lung transplantation

Abstract: Aspiration of duodenogastroesophageal refluxate is prevalent after lung transplantation and is associated with the development of BOS. Elevated BALF bile acids may promote early BOS development via an inflammatory process, possibly mediated by IL-8 and alveolar neutrophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
246
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 286 publications
(260 citation statements)
references
References 26 publications
11
246
1
2
Order By: Relevance
“…2), indicating that lymphoid neogenesis is initiated before the development of OB. Moreover, considering alloantigen-independent inflammatory stimuli such as ischemia-reperfusion injury at the time of transplantation (40), bacterial colonization in airways (41,42), and bile/acid aspiration (43,44) that contribute to OB/BOS, these Ag-independent factors might be enough to activate resident cells such as endothelial cells in airways to initiate lymphoid neogenesis. An interesting question to be answered in the future is how soon such phenotypical changes in the resident cells (e.g., endothelial cells) leading to lymphoid neogenesis start after lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…2), indicating that lymphoid neogenesis is initiated before the development of OB. Moreover, considering alloantigen-independent inflammatory stimuli such as ischemia-reperfusion injury at the time of transplantation (40), bacterial colonization in airways (41,42), and bile/acid aspiration (43,44) that contribute to OB/BOS, these Ag-independent factors might be enough to activate resident cells such as endothelial cells in airways to initiate lymphoid neogenesis. An interesting question to be answered in the future is how soon such phenotypical changes in the resident cells (e.g., endothelial cells) leading to lymphoid neogenesis start after lung transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…15 Similarly, bile acid measurement in BALF in 120 transplant recipients showed that freedom from BOS was significantly shortened in patients with elevated BALF bile acids. 16 Evidence that GERD Plays a Role in Causing or Worsening Lung Diseases, such as IPF GERD is highly prevalent and often silent in patients with IPF. 2 by 24-hour pH monitoring of 87% in 65 patients with IPF, with a prevalence of proximal reflux of 63%.…”
Section: Evaluation Of Patients With Esld Before and After Lung Transmentioning
confidence: 99%
“…There is an increased rate of acute and chronic rejection in patients with GERD. One group assayed bile acids in bronchoalveolar lavage as a marker of significant reflux, documenting bile acids in perhaps 20% of transplant recipients, a finding associated with increased neutrophils and the chemokine IL-8, as well as a clear progression to OB (68). Case reports have documented significant improve-ment in lung function after fundoplication surgery, and uncontrolled series have supported this finding (69)(70)(71).…”
Section: Operative and Perioperative Considerations In Lung Transplanmentioning
confidence: 99%
“…There remains a need to determine which factors are most useful in directing changes in pre-transplant and post-transplant patient management to improve outcome. The consensus of Conference attendees was that without clinical factors clearly predictive of outcomes, a range of biomarkers and additional potential risk factors should be considered for further multicenter investigation (35,37,38,45,46,49,68,71). For example, biomarkers of inflammation (IL-2; IL-6; IL-8; IL-10; TGF-b, etc.)…”
Section: Marlyn S Woo and Geoffrey Kurlandmentioning
confidence: 99%